Review on effect machining parameters on performance of natural fibre–reinforced composites (NFRCs). (September 2019) - Rajmohan, T; Vinayagamoorthy, R; Mohan, K
In the modern years, natural fibre composites have been converted into significant materials in many industries such as automotive, aerospace and and so on. Several types of natural fibre composites, particularly plant-based fibre composites, have been developed and tested. However, their mixed nature, engineer's requirement of experience, an understanding of machinability databases, limit setting and trouble in manufacturing are barriers to extensive use of composites. The final shape of the natural fibre–reinforced composites (NFRCs) are obtained by conventional and unconventional machining. Machining of these composites generates confront due to the heterogeneous and anisotropic nature. Different methodologies and tools are intended to overcome the machining defects. In this article, a wide range of literature review on machining of NFRCs is examined with focus on conventional and unconventional machining operation. This article also discusses the influences of machining parameters and optimum conditions for machining of NFRCs.